Holographic phase transition from novel Gauss–Bonnet AdS black holes - Hui-Ling Li; Xiao-Xiong Zeng; Rong Lin (European Physical Journal C: Particles and Fields, 2020)
Abstract In the framework of holography, we discuss on the phase transition behavior from a novel Gauss–Bonnet AdS black hole discovered in [Phys. Rev. Lett. 124, 081301 (2020)] in both charged and neutral cases. First, we explore the thermodynamic behavior for the black hole entropy by investigating $$T-S$$ T-S diagram, specific heat capacity and free energy, and we find that, in the $$T-S$$ T-S plane, the black hole exhibits a van der Waals phase transition similar to that in $$P-V$$ P-V plane in extended phase space. Secondly, we detect thermodynamic phase transition for the two point correlation function, and find that, the van der Waals phase transition can also be displayed in the $$T-δ L $$ T-δL plane which is completely similar to that of black hole entropy in the $$T-S$$ T-S plane. Our result turns out that, not only the charged but also neutral cases, we can observe holographic van der Waals phase transition for the novel Gauss–Bonnet AdS black hole by employing the black hole entropy and two point correlation function.